2008
DOI: 10.1007/s10483-008-0210-1
|View full text |Cite
|
Sign up to set email alerts
|

Entropy generation analysis of thermally developing forced convection in fluid-saturated porous medium

Abstract: Entropy generation for thermally developing forced convection in a porous medium bounded by two isothermal parallel plates is investigated analytically on the basis of the Darcy flow model where the viscous dissipation effects had also been taken into account. A parametric study showed that decreasing the group parameter and the Péclet number increases the entropy generation while for the Brinkman number the converse is true. Heatline visualization technique is applied with an emphasis on Br<0 case where there… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…Three different boundary conditions on the external surface of the channel were considered, and expressions for the Nusselt number, Bejan number and rates of entropy generation were developed. This analysis was later extended to developing flow by considering simple Darcian flow with the LTE condition, under constant temperature boundary conditions [29]. Mahmud and Fraser [30] considered constant, but dissimilar wall temperatures and conducted analytical and numerical studies on the heat transfer and entropy generation characteristics of a fully-filled channel [30].…”
Section: Introductionmentioning
confidence: 99%
“…Three different boundary conditions on the external surface of the channel were considered, and expressions for the Nusselt number, Bejan number and rates of entropy generation were developed. This analysis was later extended to developing flow by considering simple Darcian flow with the LTE condition, under constant temperature boundary conditions [29]. Mahmud and Fraser [30] considered constant, but dissimilar wall temperatures and conducted analytical and numerical studies on the heat transfer and entropy generation characteristics of a fully-filled channel [30].…”
Section: Introductionmentioning
confidence: 99%
“…In practice, the extent of these irreversibilities can be measured by the entropy generation rate. In designing practical systems, it is desirable to minimize the rate of entropy generation and to maximize the available energy Hooman et al (2008), Delavar, and Hedayatpour (2012). The entropy generation induced by natural convection heat transfer in a square cavity was studied by Shahi et al (2011) and found that the Nusselt number increased and the entropy generation reduced as the nanoparticle volume fraction was increased.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, the extent of these irreversibilities can be measured by the entropy generation rate. In designing practical systems, it is desirable to minimize the rate of entropy generation so as to maximize the available energy [7][8][9]. Overall, the results have shown that the rate of entropy generation increases as the irreversibility distribution ratio increase.…”
Section: Introductionmentioning
confidence: 99%